Development of Islamic Education Teachers' Competence in Preparing Valid and Reliable Tests at an Islamic Junior High School in Mojokerto Regency - Ainul Yaqin; Amru Al-Mu’tasim (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
One phenomenon that seems strange from the implementation of learning evaluation is the absence of a test step on the evaluation instrument (test) used to measure student learning success to get a valid and reliable tool. This assistance aims to develop the competence of MTs PAI teachers in Mojokerto Regency in increasing the development of valid and reliable tests. The method used in the community service program to develop PAI MTs Teacher Competence in Mojokerto Regency in preparing this Valid and Reliable Test uses service-learning, with preparation, service, and evaluation stages. The result of this assistance is a change in the commitment of PAI teachers and an increase in the capacity to prepare valid and reliable tests so that the quality of the PAI learning evaluation improves well.